KNOWLEDGE REGARDING RCH SERVICES AMONG HEALTH WORKERS, PREGNANT MOTHERS AND ADOLESCENTS IN RURAL FIELD PRACTICE AREA - Rashmi, Anusha; Rashmi; Kiran, N. Udaya (Journal of Health and Allied Sciences NU, 2013)
Maternal mortality and morbidity are significant health problems in developing countries. Improving maternal health has been an essential element for achieving health for all and has been included in MDG to be achieved by 2010. Apart from mothers and children, the health of adolescents came into light as one of the important area mainly because of their role as future or immediate mothers. Role of health care providers especially the grass root level workers becomes particularly important not just in imparting the intending services, but also in imparting knowledge about reproductive health.To assess the knowledge about RCH services among the health care workers, pregnant women, mothers and adolescent girls.A cross sectional study was conducted in the rural field practice areas of K. S. Hegde Medical Academy. A total of 37 health workers, 50 pregnant women and mothers and 56 adolescents were interviewed using a pre tested questionnaire for assessing their knowledge regarding RCH services. Descriptive statistics was used in the analysis.Knowledge regarding high risk pregnancy identification, normal birth weight and identifying anaemia in the field was good among health workers. Only 10.8% of them knew the minimum strength of medical officers in a FRU and only 5.4% knew about fast breathing in less than 2 months old infant. With regard to mothers knowledge 64% were aware of the number of ANC visits, 44% knew about correct interval between 2 pregnancies, 38% knew about methods to prevent STI transmission. 82% of adolescents had good knowledge regarding legal age for marriage. 75% were aware of various methods of contraception.
Keywords: RCH; Health workers; Pregnant mothers; Adolescent girls